The functional highly sensitive brain: a review of the brain circuits underlying sensory processing sensitivity and seemingly related disorders. (19th April 2018) - Acevedo, Bianca; Aron, Elaine; Pospos, Sarah; Jessen, Dana
Abstract : During the past decade, research on the biological basis of sensory processing sensitivity (SPS)—a genetically based trait associated with greater sensitivity and responsivity to environmental and social stimuli—has burgeoned. As researchers try to characterize this trait, it is still unclear how SPS is distinct from seemingly related clinical disorders that have overlapping symptoms, such as sensitivity to the environment and hyper-responsiveness to incoming stimuli. Thus, in this review, we compare the neural regions implicated in SPS with those found in fMRI studies of—Autism Spectrum Disorder (ASD), Schizophrenia (SZ) and Post-Traumatic Stress Disorder (PTSD) to elucidate the neural markers and cardinal features of SPS versus these seemingly related clinical disorders. We propose that SPS is a stable trait that is characterized by greater empathy, awareness, responsivity and depth of processing to salient stimuli. We conclude that SPS is distinct from ASD, SZ and PTSD in that in response to social and emotional stimuli, SPS differentially engages brain regions involved in reward processing, memory, physiological homeostasis, self-other processing, empathy and awareness. We suggest that this serves species survival via deep integration and memory for environmental and social information that may subserve well-being and cooperation. This article is part of the theme issue 'Diverse perspectives on diversity: multi-disciplinary approaches to taxonomies of individual differences'.